Targeting epigenetic mechanisms for clinical translation: enhancing the efficacy of tumor immunotherapies. (November 0201) - Kosoff, David; Krueger, Timothy; Lang, Joshua M
The ability to evade host immune surveillance is critical for the survival of tumor cells and is correlated with poor clinical outcomes. Many tumor types have been found to downregulate expression of genes involved in antigen production, processing and presentation to evade immune detection. Recent findings suggest that the mechanisms underlying these immune evasion phenomena extend beyond alterations in DNA sequence to include epigenetic modifications of DNA and associated proteins, including hypermethylation of DNA and altered histone acetylation patterns. This review will summarize alterations in antigen presentation machinery identified in malignant cells, epigenetic mechanisms that can be employed in the downregulation of genes relevant for antigen presentation and translational strategies to target these processes to enhance the efficacy of antitumor immunotherapies.